Jenis Kelamin Perempuan Memiliki Keterampilan Cuci Tangan yang Baik pada Anak Usia Sekolah - Filia Sofiani Ikasari; Agus Setiawan; Sukihananto Sukihananto (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2020)
Introduction: School-age children were children in the age range of 6 to 12 years and in this age range children have risk of contracting various diseases because children spend a lot of time at school. These diseases can be prevented by practicing proper hand washing. One of the predisposing factors of hand washing behavior was gender, but there are no results of research that agree on the relationship between gender and the correct practice of hand washing in school-age children. Objective: This study aims was to determine the relationship between gender and the correct practice of hand washing in school-age children Method: This study used a cross-sectional study design conducted at the Jawa 5 Elementary State School in Martapura. Respondents were elementary school students in grades II, III, IV and V, as many as 393 people were obtained using simple random sampling techniques. Data analysis used Pearson Product Moment test. The instruments of this study used a questionnaire. Result: The results showed that there was a significant relationship between gender and correct hand washing practices (p value <0.05). Conclusion: School-age children with female sex have more handwashing practice scores and there is a relationship between sex with correct hand-washing practices in school-age children